PENGUATAN PENDIDIKAN KARAKTER UNTUK MENGURANGI KASUS BULLYING PADA SISWA DI SD 04 PATAMUAN PADANG PARIAMAN - Zahara, Leni; Afdal, Muhammad; Ramayuli, Nisa; Nofriyani, Rheza; Putri, Sherly Kurnia; Putri, Sridevi Insani Cahaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is the main foundation in driving the progress of the nation, yet the phenomenon of bullying remains a serious challenge in Indonesian education. This study aims to describe the implementation of character education reinforcement in reducing cases of bullying among students at SD 04 Patamuan Padang Pariaman. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation, where teachers are the main population of the research. The results show that there are many forms of bullying, including verbal ridicule, calling parents' names, and social exclusion. Prevention efforts are carried out through the